2003
DOI: 10.1016/s0194-5998(03)00469-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of middle meatal stenting after minimally invasive sinus techniques (mist)

Abstract: Compared with Gelfilm, Merogel MM stents produced less synechia; Merogel retains its position in the MM longer than Gelfilm; and the incidence of postoperative MM synechia can be reduced when absorbable MM stents are used in conjunction with MIST.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 18 publications
4
56
2
Order By: Relevance
“…We found no statistically significant difference in infection score at any postoperative visit. This result was similar to the results reported by others [11,20]. The difference in infection rate between the Meropack-dressed and unpacked sinuses was not statistically significant, which could have been due to the bacteriostatic effect of Meropack [21].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We found no statistically significant difference in infection score at any postoperative visit. This result was similar to the results reported by others [11,20]. The difference in infection rate between the Meropack-dressed and unpacked sinuses was not statistically significant, which could have been due to the bacteriostatic effect of Meropack [21].…”
Section: Discussionsupporting
confidence: 91%
“…Catalano and Roffman reported the infection rate was 6.4% (6/94) among both Merogel and Gilfilm groups at the first postoperative visit, and that both groups had 0% infection rates at later visits [11]. Miller et al found no statistically significant difference in infection between hyaluronic acid and non-absorbable packing at any follow-up visit [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a nonrandomized, uncontrolled study, Catalano and Roffman [10] reported that 86% of the sides that had a different HA gel packing (Merogel; Medtronic Xomed, Jacksonville, Fla., USA) placed with a Gelfilm stent did not develop synechiae. In a series of 10 patients, Kimmelman et al [11] demonstrated that a different HA gel sinus dressing (Sepragel; Genzyme) was effective at decreasing synechiae and middle meatal stenosis while improving pain in the early postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…46 Discussion of the reasons for different surgical techniques is beyond the scope of this review; however, it is important to examine the surgical ostium for postoperative narrowing as a result of synechiae, edema, thickened mucus, fungus balls, or polyps. [47][48][49] The thickness of the lateral nasal wall at the margin of the surgical ostium should also be noted. This wall is usually a thin structure.…”
Section: Patency Of the Surgical Ostiummentioning
confidence: 99%